Clinical relevance of gastroesophageal cancer associated SNPs for oncologic outcome after curative surgery - Jung, Jin-On; Wirsik, Naita Maren; Nienhüser, Henrik; Peters, Leila; Müller, Beat P.; Heß, Timo; Schüller, Vitalia; Schumacher, Johannes; Schmidt, Thomas (Annals of surgical oncology, 2022)
Gastric and esophageal cancers are malignant diseases with rising importance in Western countries. To improve oncologic outcome after surgery, it is essential to understand the relevance of germline mutations. The aim of the study was to identify and distinguish clinically relevant single-nucleotide polymorphisms (SNPs).
Gesehen am 31.07.2023